(untitled) (Latakia University Journal -Engineering Sciences Series, 2023)
Rock squeezing causes additional loads on the deep tunnels, and the intensity of these loads increases with time, especially when the strength of the rock surrounding the tunnel is weak compared to the overburden pressure. This research aims to analyze the causes of the failure of tunnel of 16th Tishreen Dam, with the proposal of appropriate rehabilitation measures. The tunnel was subjected to various deformations, including buckling and spalling of sidewalls, floor heave and extremely large convergence reaching failure state of tunnel lining. For this purpose, the research was carried out in three stages: the technical reports were firstly reviewed parallel to geotechnical investigation of surrounding soil. Later, the main and secondary causes of deformations were analyzed and the tunnel’s vulnerability to the rock squeezing phenomenon was evaluated according to empirical equations. the third stage proposed appropriate rehabilitation measures. These measures included a rigid supporting system consisting of: closed steel ribs (IPE200), grout injection, ground anchors and new lining of reinforced concrete consisting of shotcrete layer and and a second layer of cast-in-place concrete. Consequently, the main causes of large deformation were identified and the heavy support system is verified to control the deformation and put the tunnel into service again.